Ensino de ciências na educação infantil: formação de professores da rede municipal de ensino de Santa Maria, RS, Brasil - Botega, Marcia Palma (2015)
The science education has assumed an important role in basic education, curriculum guidelines point to the importance of the world of knowledge of the area to the full development of students through the awareness of the scientific literacy. However, some studies indicate that teachers do not attach enough importance to this area and infer that this position may be due to the uncertainty of these professionals who, in turn, may be associated with deficiencies in training related to science teaching during his academic route. Research in this qualitative study, exploratory about the objectives, using action research on the technical procedures involved 73 teachers of early childhood education in the city of Santa Maria, RS, Brazil. To develop the study took into account three times: at first there was the characterization of the training needs of teachers for the teaching of science in early childhood education; from the identified needs, organized a guide of teaching experiments; subsequently held theoretical and practical workshops, using the constant experiments in the teaching guide. The data collected and later analyzed showed the need for training in science, these professionals. Thus, it can be concluded that the study had a positive impact as it allowed these teachers understand the importance of the approach of science in early childhood education and pique your interest for didactic and pedagogic practices that privilege in context with other areas of knowledge, completion of the experimental work by research in science teaching.